Malnutrition among under-five children in amhara and oromia regions, Ethiopia: Continuous time markov multi-state modeling - Dafa Duge Wachifo; Dereje Danbe Debeko; Zeytu Gashaw Asfaw (PLoS ONE, 2025)
Background Ethiopia faces a high burden of undernutrition prevalence, ranking among the 15 worst-affected nations globally. So, this study aimed to find out how often and how long under-five children (U5C) in Ethiopia’s Amhara and Oromia regions move between different states of Composite Index Anthropometry Failure (CIAF) as well as what factors influence these changes. Methods The data used for this study was extracted from the International Food Policy Research Institute. The institute conducted a follow-up survey in three consecutive rounds: February 8, 2018–April 25, 2018; July 25, 2019–October 23, 2019; and February 8, 2021–April 25, 2021, respectively. The inclusion criteria were households that had children between the ages of 0 and 35 months, were participants in the safety net program, and had the mother or primary female caregiver during the baseline survey. A total of 3,044 households having children with at least two complete anthropometric measurements were included. A continuous-time multi-state Markov model was used to estimate transitions and their probability between CIAF’s states. Results Nourished children had a 71% probability of becoming undernourished. Time taken to recover from undernourished state for U5C was 41 months on average. 75% of the U5C’s life is spent in the undernourished state. Girls had a 1.824 times higher likelihood of recovering from an overnourished state and were less likely to transit from a nourished state to an undernourished state compared to boys (HR: 0.8013). Children older than two years were more likely to recover from undernourished and overnourished states respectively (HR: 1.013 & 1.036), to a nourished state and less likely to transit back to the malnutrition states (HR: 0.9693 & 0.9662). Children of educated mothers and residents in the Oromia region had lower risk of transition from a healthy to an undernourished state respectively (HR: 0.8171& 0.8074). Conclusion Undernutrition will affect most U5Cs. Children whose mothers had no education and live in the Amhara region are more susceptible to undernutrition. The Ministry of Health and other relevant stakeholders should develop a practical intervention to enhance adult and maternal education programs.